2013
DOI: 10.1017/s0022215113001588
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of paediatric laryngeal papillomas: web survey of British Association of Paediatric Otolaryngologists

Abstract: There was no consensus as to when it would be appropriate to use cidofovir, indicating the need for cidofovir usage guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Lasers and microdebriders are both efficient techniques for respiratory papillomatosis to the extent that cold steel excision of laryngeal papillomatosis is seldom performed these days. 14 In the current study, microdebrider was found to be superior in some aspects, although it was equal to but not less than CO2 lasers in many other aspects. Certain disadvantages are associated with CO2 lasers.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Lasers and microdebriders are both efficient techniques for respiratory papillomatosis to the extent that cold steel excision of laryngeal papillomatosis is seldom performed these days. 14 In the current study, microdebrider was found to be superior in some aspects, although it was equal to but not less than CO2 lasers in many other aspects. Certain disadvantages are associated with CO2 lasers.…”
Section: Discussionmentioning
confidence: 42%
“…1 The use of microdebriders among otolaryngologists is increasing due to its ability to remove large tissue chunks with simultaneous suctioning. 14 But access to specific regions, like anterior commissure and vocal folds, via microdebrider is difficult. Lasers are effective in excising sessile masses from anterior commissure and vocal folds.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is a trend amongst otolaryngologists in the United Kingdom towards the use of microdebriders for endoscopic resection of RRP . Although this study has identified no difference in impact on disease burden between patients undergoing microdebrider surgery vs those undergoing CO 2 laser surgery, there is a significant reduction in operative time with the use of the microdebrider, potentially impacting on operating theatre costs.…”
Section: Discussionmentioning
confidence: 72%